Reiszlamizációs folyamatok a Balkánon, különös tekintettel Bulgáriára - Bacsa, Beatrix; M. Császár, Zsuzsanna (Közép-Európai Közlemények, 2014)
The intention to create a multicultural society is a real challenge not just for the Western-European countries but for all European countries having different ethnical groups of people with different cultural or religious roots. The Western countries have never looked at the Balkan region as the part of Europe, since this region has been deemed a crucial focus-point of the continent which is a continuous threat for maintaining the peace and the balance created. As it is obvious the Balkan region is the place of interlock of different ethnical groups and religions, where an existence of a nation was determined not by the same ethnical origin but rather by the same religion. Among the three major religions existing in the Balkan region, the number of the followers of the Islam shows an increasing tendency. The reason of it on one hand is the demographic growth of the Muslims and on the other hand the resurgence of the religious identity. The reislamisation process is clear and present especially in the area inhabited by Bosnian people, or amongst the Turkish people living in Bulgaria, where, in order to spread the Muslim religion, several schools have been opened and there is an ever-growing emphasis on showing the religious commitment in externals and appearance as well. The spread of the religious ideology in the Balkan region was followed by the appearance of extreme Islamic trends therefore the analysis of the issue of the threat of terrorism in the region is inevitable.